Karakterisasi Kerusakan Fisik, Proses Pembusukan dan Jamur Pembusuk pada Buah dan Sayur - Rahmiati, Rahmiati; Situmorang, Toberni S; Simanjuntak, Helen Anjelina; Karnina, Sisca; Fadilla, Zahira (Journal of Natural Sciences, 2024)
Physical damage and post-harvest decay in fruits and vegetables are common issues that can reduce product quality and shelf life. This study aims to understand the decay process and characteristics of spoilage fungi in several types of fruits and vegetables. This descriptive qualitative research used the streak plate isolation method and block square identification. The samples used included salak, grapes, oranges, potatoes, long beans, and cabbage, all of which were fresh and of good quality. Each sample was weighed to 50 gr and placed in a sterile container. Observations of the physical characteristics of the samples were conducted from day 2 to day 8, including identifying the growing spoilage fungi. The results showed the presence of six spoilage fungi coded as JPS1, JPA1, JPJ1, JPK1, JPP1, and JPU1 from each sample. These fungi exhibited varying morphological characteristics based on colony color, spore color, and fungal size. Identification revealed that isolates JPS1, JPA1, JPJ1, and JPU1 belong to the genus Aspergillus sp., isolate JPK1 to the genus Trichocladium sp., and isolate JPP1 to the genus Rhizopus sp.